2010
DOI: 10.3109/08037051.2010.483055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HIV duration on ambulatory blood pressure in HIV-infected individuals with high office blood pressure

Abstract: HIV duration was an independent predictor of ABP and hypertension in a selected group of HIV-infected individuals. Nocturnal hypertension was prevalent, and white coat hypertension was present in one fourth of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 44 publications
0
12
1
Order By: Relevance
“…It has been suggested that the use of HAART may be associated with increasing blood pressure [9, 10, 35, 36]. In some studies, longer time of HAART was associated with hypertension [13, 37]. These associations were not identified in our study, since the use of antiretrovirals, time of HIV infection, AIDS, and CD4 count were not associated with hypertension.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…It has been suggested that the use of HAART may be associated with increasing blood pressure [9, 10, 35, 36]. In some studies, longer time of HAART was associated with hypertension [13, 37]. These associations were not identified in our study, since the use of antiretrovirals, time of HIV infection, AIDS, and CD4 count were not associated with hypertension.…”
Section: Discussioncontrasting
confidence: 69%
“…Hypertension prevalence in HIV-infected individuals ranges from 5.9 to 56.4% [912] and has been associated with alcohol abuse and other factors related to HIV infection [9, 10, 13]. In these individuals, the prevalence of alcohol abuse ranges from 8% [14, 15] to 50% [16–18], exceeding the rates in general populations of the United States [19], Europe [20], and Brazil [21], where the prevalence is between 2 and 41% in men and 0.1 and 21% in women [20].…”
Section: Introductionmentioning
confidence: 99%
“…Our study found that increasing duration of HIV infection, above that associated with increasing age, was associated with hypertension in our multivariate models. 26 HIV infection has been linked to arterial stiffness and proinflammatory responses 27 ; hence, the virus may lead to premature vascular dysfunction causing elevated blood pressure. Beyond endothelial dysfunction and accelerated vascular aging, subclinical HIV-associated kidney effects may also explain the high rates of hypertension among HIV patients 17 ; further studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Both prevalent hypertension and ambulatory hypertension (i.e. hypertension defined based on daytime ambulatory blood pressure (ABP)) has been independently related to duration of HIV infection [84,101].…”
Section: Hypertension In Hiv-infected Individualsmentioning
confidence: 99%